The experience of the using of sociological method «feedback» on the realization of the tasks of the educational quality’s increasing in the medical university - Injigolyan, A.A.; Lamanova, A.S. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The article is devoted to the analysis of the practice of the problems’ solving in the improvement of the quality of educational services provided by higher educational institutions of the Republic of Kazakhstan on the example of the Karaganda Medical University. One of the aspects of effective implementation of improving the quality of education is the introduction of elements of sociological monitoring of ongoing reforms in the university management system, through the method of studying «feedback». The authors of the article describe the results of the sociological research conducted at the university, draw conclusions about the heuristic and scientific possibilities of using this method for solving the issues of obtaining an assessment of the quality of education by the participants in the educational process, analyzing the advantages and disadvantages, the «strong» and «weak» sides of the educational process, summarizing and correction of individual elements of the management of the learning process. There is written the conclusion in the article that in Karaganda State University the possibility of using the sociological method of obtaining «feedback» is used as widely and effectively as possible.
Медициналық жоғарғы оқу орынында білім беру сапасын арттыру міндеттерін жүзеге асыруда «кері байланыс» əлеуметтік əдістемені қолдану тəжірибесі
Опыт использования социологической методики «обратной связи» при реализации задач повышения качества образования в медицинском вузе
Keywords: education; quality of education; sociological research; educational process; research methods; «feedback»